1998
DOI: 10.1093/bja/81.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative pharmacokinetics of transdermal fentanyl in elderly and young adult patients

Abstract: The perioperative pharmacokinetics of transdermally-delivered fentanyl were compared in 10 young adult (mean [range] age 32.7, [25-38] yr) and eight elderly (mean [range] age 73.7 [64-82] yr) patients following abdominal surgery. Transdermal fentanyl patches designed to release 50 micrograms h-1 were applied 2 h preoperatively and left in place for 72 h. Plasma fentanyl concentrations were measured by radioimmunoassay during patch application and for 30 h after patch removal. The mean half-time (time for plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 11 publications
3
29
0
3
Order By: Relevance
“…O ajuste da analgesia após procedimentos cirúrgicos não consiste apenas no tratamento da dor, pois também se faz necessário o controle dos efeitos adversos, de forma que estes estejam ausentes ou possam ser contornados sem lesão ao paciente. A analgesia com o fentanil transdérmico é feita sem o uso de agulhas e apresenta farmacocinética similar ao uso do fármaco por via venosa, e a concentração plasmática de fentanil se mantém constante durante o período de aplicação do adesivo, por até 72 horas 4 . Estudos comparando ambas as apresentações, sob o ponto de vista farmacocinético, demonstraram meia-vida e concentração máxima semelhante entre a infusão contínua e o adesivo 11 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O ajuste da analgesia após procedimentos cirúrgicos não consiste apenas no tratamento da dor, pois também se faz necessário o controle dos efeitos adversos, de forma que estes estejam ausentes ou possam ser contornados sem lesão ao paciente. A analgesia com o fentanil transdérmico é feita sem o uso de agulhas e apresenta farmacocinética similar ao uso do fármaco por via venosa, e a concentração plasmática de fentanil se mantém constante durante o período de aplicação do adesivo, por até 72 horas 4 . Estudos comparando ambas as apresentações, sob o ponto de vista farmacocinético, demonstraram meia-vida e concentração máxima semelhante entre a infusão contínua e o adesivo 11 .…”
Section: Discussionunclassified
“…Um dos fatores que contribuem para a inadequada analgesia é a ocorrência de dor nos intervalos entre a administração de doses de analgésicos e os efeitos adversos 3 . O fentanil administrado por via transdérmica, que apresenta farmacocinética similar ao uso por via venosa com a concentração plasmática se mantendo constante durante o período de até 72 horas 4 , tem se mostrado um método seguro e efetivo no manuseio da dor crônica, e também tem sido usado para promoção de analgesia também na dor aguda 5,6 . O objetivo deste estudo foi avaliar a analgesia proporcionada pelo uso do fentanil transdérmico na dor aguda pós-operatória em pacientes submetidos à cirurgia de artrodese de coluna, bem como observar a incidência de efeitos adversos relacionados ao seu uso.…”
Section: Introductionunclassified
“…Older patients should not receive agonist-antagonist agents that avoid mu-opioid receptor binding. Transdermal fentanyl patches demonstrate delayed absorption in elderly individuals with decreased subcutaneous fat stores, and may require careful monitoring during initial titration and dose increases [60]. An opiate-naïve patient should not be started on more than 25 µg of fentanyl, and this dose may be too high for initiation of opioid therapy in some frail elderly individuals.…”
Section: Opioidsmentioning
confidence: 99%
“…In a study of a transdermal patch delivering fentanyl at 50 µg·h Ϫ1 , for 72 h, it was found that the time to maximum plasma concentrations, elimination half-life, and area under the time concentration curve did not differ significantly between elderly and young adults [141]. In children aged 18 to 60 months, time (SD) to reach maximum concentration was 18 (11) h with a patch designed to release fentanyl at 25 µg·h Ϫ1 for 72 h. As would be expected, maximal fentanyl concentrations were higher in younger children [142].…”
Section: Transdermal Routementioning
confidence: 99%